SEPARATION OF U234 AND U238 DURING CONCENTRATION OF URANIUM ON DIFFERENT SORBENTS FROM SOME NATURAL WATERS - Chalov P.I.; Merkulova K.I.; Mamyrov U.I. (My University, 1988)
For the first time that fractionation of U234 and U238 can occur under certain specific conditions when uranium passes from the liquid phase to the solid. It was discovered accidentally during an investigation of the efficiency of uranium concentration by different sorbents from some thermal mineral waters of southern Georgia. The phenomenon of isotopic fractionation of uranium during its sorption from some natural waters does not result from the differences in atomic weight, because no such effect was observed for U235. All available information suggests that the thermal mineral waters studied are 'disequilibrium' chemical systems, in which uranium with different excess of U234 occurs in different chemical forms - ionic, colloidal and the like. These different forms of uranium arise when ground water seeps through rocks and remain (i.e., without converting to a single form) until it emerges at the surface.